2007
DOI: 10.1002/rra.1030
|View full text |Cite
|
Sign up to set email alerts
|

Fish zonation and indicator species for the evaluation of the ecological status of rivers: example of the Loire basin (France)

Abstract: In the context of river alteration, ecologists are asked to develop tools for the assessment of river integrity. Fish are known to be good bioindicators of the ecological condition of rivers. The Loire basin (France) is often considered as relatively little impacted compared to most other large European systems. But curiously, no study clearly addressed the question of fish assemblages patterns in this system in order to assess this status. Thus, we studied fish assemblages along the river network in the Loire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 58 publications
7
99
0
6
Order By: Relevance
“…Faced with the widespread problem related to the difficulty of obtaining reliable and usable data sets, recent advances in conservation biology have suggested that presence-absence data are particularly suitable for the assessment of species distribution in a conservation context (MacKenzie, 2005;Vojta, 2005). Despite the simplicity of such input data, they can provide reliable information for analyzing species distribution, especially in a conservation context (Joseph et al, 2006), and above all the distributions of fish assemblages (Ibarra et al, 2005;Lasne et al, 2007aLasne et al, , 2007b, certain fish species (Oberdorff et al, 2001;Pont et al, 2005), migratory fishes (Eikaas and MacIntosh, 2006) and eel (Broad et al, 2001;. In fish, electrofishing methods are among the most common ways of sampling fish.…”
Section: > Assessing Distribution Patterns With Logistic Modelsmentioning
confidence: 99%
“…Faced with the widespread problem related to the difficulty of obtaining reliable and usable data sets, recent advances in conservation biology have suggested that presence-absence data are particularly suitable for the assessment of species distribution in a conservation context (MacKenzie, 2005;Vojta, 2005). Despite the simplicity of such input data, they can provide reliable information for analyzing species distribution, especially in a conservation context (Joseph et al, 2006), and above all the distributions of fish assemblages (Ibarra et al, 2005;Lasne et al, 2007aLasne et al, , 2007b, certain fish species (Oberdorff et al, 2001;Pont et al, 2005), migratory fishes (Eikaas and MacIntosh, 2006) and eel (Broad et al, 2001;. In fish, electrofishing methods are among the most common ways of sampling fish.…”
Section: > Assessing Distribution Patterns With Logistic Modelsmentioning
confidence: 99%
“…The Loire itself is a relatively freeflowing river, and there are no significant barriers to migration in its lower reaches (the first one is > 500 km upstream of the tidal limit). Consequently, the Loire basin is often considered as being less impacted than other large river systems in Europe (Lasne et al, 2007). In contrast, most of its tributaries have been largely regulated by barriers that fish may or may not be able to get through.…”
Section: > Study Areamentioning
confidence: 99%
“…With regard to the continental yellow eel stage in the Loire, the eel distribution could be obtained from the sampling network of the ONEMA (the French National Office for Water and the Aquatic Environment), which covers 135 sites around the Loire catchment basin. This identified the most important eel sectors, and provided an indication of current densities, and of spatial and temporal trends (Lasne et al, 2007;Lasne and Laffaille, 2008). These densities made it possible to identify the administrative areas (departments) around the Loire that were most implicated in the management of the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish ecology, the structure of fish assemblages depends on many interacting factors and can be quantified by summarizing species richness, composition and feeding guilds (Karr, 1981). Classification of sites (or areas) based on fish species assemblages has been elaborated for many lotic systems (Konan et al, 2006;Park et al, 2006;Kruk et al, 2007;Lasne et al, 2007). Modelling the composition of fish assemblages on the basis of biotic and abiotic environmental descriptors is an important aspect of the management of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%